2022
DOI: 10.1155/2022/1764104
|View full text |Cite
|
Sign up to set email alerts
|

Acupoint Catgut-Embedding Therapy Inhibits NF-κB/COX-2 Pathway in an Ovalbumin-Induced Mouse Model of Allergic Asthma

Abstract: Allergic asthma is associated with T helper (Th) 2 cell-biased immune responses and characterized by the airway hyperresponsiveness (AHR). Studies have shown that the acupoint catgut-embedding therapy (ACE) has a therapeutic effect on allergic asthma. However, the relevant mechanism is poorly understood. In present study, female BALB/c mice were sensitized and challenged with ovalbumin (OVA) to establish a model of allergic asthma. AHR was evaluated by using airway resistance ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In our experimental results, qPCR experiments showed that the levels of cytokines in 16-HBE cells decreased with the up-and downregulated changes of CYCS, indicating that cytokines (CCL-17, IL-5, IL-8, and COX-2) are positively regulated by CYCS. In recent studies on asthma, anti-IL-5 therapy has been shown to slow the exacerbation of eosinophilic severe asthma, IL-8 antagonism can be used in the treatment of asthma, and COX-2 is also associated with allergic asthma [41][42][43]. This findings might offer new directions for the development of asthma immunotherapy.…”
mentioning
confidence: 99%
“…In our experimental results, qPCR experiments showed that the levels of cytokines in 16-HBE cells decreased with the up-and downregulated changes of CYCS, indicating that cytokines (CCL-17, IL-5, IL-8, and COX-2) are positively regulated by CYCS. In recent studies on asthma, anti-IL-5 therapy has been shown to slow the exacerbation of eosinophilic severe asthma, IL-8 antagonism can be used in the treatment of asthma, and COX-2 is also associated with allergic asthma [41][42][43]. This findings might offer new directions for the development of asthma immunotherapy.…”
mentioning
confidence: 99%
“…An asthma model showed that stimulation at GV14, BL13, and BL12 could increase IFN-γ in the BALF and lung tissue. 44 GV14, BL13, and ST36 are another acupuncture formula and could reduce cytokines related to Th2, such as IL-4 and IL-5, through elevating the level of T-bet, thereby controlling the differentiation of Th1 and inhibiting cytokine synthesis in Th2. 50,51 Treg/Th17 balance as a marker of non-type 2 inflammation, and severe asthma often exists in specific groups, such as obesity, cancer, and even in glucocorticoid resistance.…”
Section: Pulmonary Group 2 Innate Lymphoid Cellsmentioning
confidence: 99%
“… 41 TSLP, IL-9, IL-4, and IL-13 also act on airway epithelial cells, impairing the epithelial further, and impair airway smooth muscle cells (ASMCs), inducing their migration and proliferation. 41 , 42 Acupuncture at GV14, Feishu BL13, and BL12 reduces IL-4, IL-5, IL-9, and IL-13 in bronchoalveolar lavage fluid (BALF) and serum, 43 , 44 and certain chemokines that control differentiation and polarization of immune cells (such as CCL1, CCL5, and CCL11) are also reduced in serum. 45 , 46 An imbalance of cytokines breaks the vessel barrier by inducing the expression of key adhesion molecules such as vascular cell adhesion protein 1 (VCAM-1) or intercellular adhesion molecule 1 (ICAM-1).…”
Section: Authenticated and Reasonable Mechanism Of Acupuncturementioning
confidence: 99%
“…After obtaining the sensation, the acupuncture needle is pushed in while withdrawing the sterile needle, leaving the catgut within the acupuncture point (4). Researches have shown that embedding catgut in specific parts of the skin (acupoint catgut embedding therapy) can continuously generate benign stimulation, affect neurotransmitters and local circulation, repair damaged neural loop networks, restore normal central function, regulate immunity, and inhibit the release of inflammatory factors (5)(6)(7). Besides, our early works and others have demonstrated that inflammation plays an important role in the development of VD (8)(9)(10)(11).…”
Section: Original Articlementioning
confidence: 99%